SAM: Semi‐Active Mechanism for Extensible Continuum Manipulator and Real‐Time Hysteresis Compensation Control Algorithm - Park, Junhyun; Jang, Seonghyeok; Park, Myeongbo; Park, Hyojae; Yoon, Jeonghyeon; Hwang, Minho (The international journal of medical robotics + computer assisted surgery, 2024)
ABSTRACT Background Cable‐driven continuum manipulators (CDCMs) enable scar‐free procedures but face limitations in workspace and control accuracy due to hysteresis. Methods We introduce an extensible CDCM with a semi‐active mechanism (SAM) and develop a real‐time hysteresis compensation control algorithm using a temporal convolution network (TCN) based on data collected from fiducial markers and RGBD sensing. Results Performance validation shows the proposed controller significantly reduces hysteresis by up to 69.5% in random trajectory tracking test and approximately 26% in the box pointing task. Conclusion The SAM mechanism enables access to various lesions without damaging surrounding tissues. The proposed controller with TCN‐based compensation effectively predicts hysteresis behaviour and minimises position and joint angle errors in real‐time, which has the potential to enhance surgical task performance.